The influence of firm- and manager-specific characteristics on the structure of executive compensation - Ryan, Harley E.; Wiggins, Roy A. (Journal of Corporate Finance, 2001)
We analyze the influence of firm and managerial characteristics on executive compensation. Consistent with theory, we find monitoring difficulties result in greater use of options while CEO and blockholder ownership result in less. Risky investment is positively related to options and negatively related to cash bonus and restricted stock, suggesting that firms use options to encourage managers to take risks. We find a negative (positive) relation between options and leverage (convertible debt) consistent with minimizing the agency costs of debt. Finally, we provide new evidence on managerial horizon and incentives, documenting a concave relation between cash bonus and CEO age.